Pneumatic dilation versus laparoscopic Heller myotomy for the treatment of achalasia: variables related to a good response. Issue 1 (1st January 2014) - Borges, A. A.; Lemme, E. M. de O.; Abrahao, L. J.; Madureira, D.; Andrade, M. S.; Soldan, M.; Helman, L.
Summary: Achalasia is a motor disorder characterized by esophageal aperistalsis and failure of lower esophageal sphincter relaxation. The cardinal symptoms are dysphagia, food regurgitation and weight loss. The most effective treatments are pneumatic dilation (PD) of the cardia and Heller esophageal myotomy with partial fundoplication. There is still controversy regarding which treatments should be initially done. The aims of this study were to evaluate clinical response and the variables related to good results in both treatments. Ninety-two patients with achalasia diagnosed by esophageal manometry were randomized to receive either PD or laparoscopic Heller myotomy with partial fundoplication. After the procedure, patients were followed up clinically and submitted to esophageal manometry and pH monitoring. Three months after treatment, 73% of the patients from PD group and 84% of the surgery group had good results ( P = 0.19). After 2 years of follow-up, 54% of the PD group and 60% of the surgery group ( P = not significant) were symptom free. Variables related to a good response to PD were a 50% drop in lower esophageal sphincter pressure (LESP) or a LESP <10 mmHg after treatment. Patients over 40 years old with LESP ≤32 mmHg before treatment and a drop in LESP >50% after treatment significantly achieved better responses after surgical treatment when compared with PD. The reflux rate was significantly higher in the PD group (27.7%) compared with the surgery group (4.7%), P = 0.003. We concluded that surgical treatment and PD for achalasia are equally effective even after 2 years of follow-up. The choice of treatment for achalasia should be based on the following parameters: treatment availability, rate of good results, complication rates, variables related to good responses and also the patient's wish.